Driving Circular Economy Disclosure: The Strategic Role of Internal Control and Organizational Resources - Sri Handayani; Bambang Sutopo (Dinasti Publisher, 2025)
This study provides empirical evidence on the role of internal control in enhancing the impact of organizational resources on Circular Economy Disclosure. Employing a quantitative approach, the research analyzes panel data from integrated reports of companies operating in circular economy priority sectors listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. Moderated Regression Analysis (MRA) is used to assess cross-sectional and time-series variations. The results reveal that both internal control and slack resources have a negative effect on CED, indicating that excessive unused resources and rigid control systems may hinder transparency. Managerial ability is found to have no significant effect on CED. However, internal control positively moderates the relationship between slack resources and CED, suggesting that effective control mechanisms can help redirect idle resources toward more strategic and transparent reporting. The implications of this study highlight that managers should strategically reallocate slack resources and implement adaptive internal controls to improve circular economy disclosure. Enhancing transparency through data integration and proactive control is key to improving reporting quality and accountability. Theoretically, the study extends RBV and contingency theory by showing how internal control shapes resource effectiveness in sustainability disclosure.